Two Cultures of Rights : the Quest for Inclusion and Participation in Modern America and Germany. - Berg, Manfred (Publications of the German Historical Institute., 2002)
This book addresses key issues in the historical struggle for civil rights, political rights, and social rights in the USA and Germany from the late nineteenth century to the present. Issues include the rights of women and minorities, National Socialism, and the emergence of the concept of social rights.